Effective work-function control technique applicable to p-type FinFET high-k/metal gate devices. (May 2017) - Yamaguchi, Shimpei; Bayindir, Zeynel; He, Xiaoli; Uppal, Suresh; Srinivasan, Purushothaman; Yong, Chloe; Choi, Dongil; Joshi, Manoj; Yang, Hyuck Soo; Hu, Owen; Samavedam, Srikanth; Sohn, D.K.
Abstract: In this work, we investigated the effect of so-called WF (Work Function) setting anneal (high temperature annealing on TiN/HfO2 stack) on gate stack properties. It was found that intermixed layer created in-between TiN and HfO2 during WF setting anneal has negative fixed charge and reduces pFET Vt (positive Vt shift). In addition, higher anneal temperature further reduces pFET Vt while keeping nFET Vt almost unchanged. This could be explained by passivation of oxygen vacancies in HfO2 with diffused oxygen from TiN layer. By combining these effects, one can further push effective work function towards valence band edge which enables wider coverage of transistor Vt option. Highlight: In this work, techniques to lower pFET Vt have been investigated. HfTiONx interfacial layer in-between HfO2 and TiN reduces pFET Vt with its negative fixed charges. Diffused oxygen from TiN layer passivates positively charged oxygen vacancies in HfO2 during anneal and reduces pFET Vt . NBTI was significantly improved with higher anneal temperature likely due to reduction of hole trapping site in HfO2 .